Investigation on the Lu-Kumar queueing network - Cheung, Wai Lun (2014)
Multi-class re-entrant networks are common in semiconductor, communication and other complex manufacturing systems. The project seeks to investigate the Lu-Kumar re-entrant queueing network through simulation. The Lu-Kumar network is a simple re-entrant system used as a starting point in examining multi-class queueing networks. Insights gained through simulation can have potential application in improving manufacturing systems.